EVALUATION OF CREAM FORMULATION FROM NANOEMULSION Euphorbia tirucalli L. WITH STEARIC ACID VARIATIONS - Meylani Nur Intan; Aldesra Fitri; Iqlima Ayu Prestisya (BRIN - Badan Riset dan Inovasi Nasional, 2026)
The macerate of Euphorbia tirucalli L. contains alkaloids, flavonoids, saponins, steroids, terpenoids, and tannins with antibacterial potential for acne management. This study formulated a nanoemulsion of E. tirucalli extract via the high-energy method, which was incorporated into cream formulations with varying stearic acid concentrations (F1;7.5%, F2;9%, F3;12%, F4;14.5%) and physical quality evaluation was carried out. The physical quality test of the cream preparations found that concentrations of stearic acid significantly affected the organoleptic properties (color and skin feels after application), spreadability 4.86-6.55 cm, water washability 8.5-19.1 mL, and viscosity 15557-31433 cPs. Meanwhile, homogeneity, phase separation, and pH of the preparation were not found the significantly different. An increase in stearic acid was directly proportional to washability and viscosity, but inversely proportional to spreadability. The formulations met the physical criteria for an acceptable cream preparation, except for pH, which was excessively alkaline. F2 and F3 establishing them as the most suitable formulations for further development. The antibacterial test against Propionibacterium acnes using the well diffusion agar assay, resulted; positive control (Mediklin; clindamycin 0.01%) in strong activity, 5% extract was in the weak activity, 10% and 20% extract was in moderate activity, 30% extract showed strong activity which is comparable to the positive control, and 20% nanoemulsion had no activity. The Spearman’s Rho test confirmed a strong correlation between extract concentration and antibacterial potency (r = 0.927).